Интеграция этапов жизненного цикла изделий машиностроения - Анипко, О. Б.; Бусяк, Ю. М.; Баулин, Д. С.; Цебрюк, И. В. (НТУ "ХПИ", 2010)
In article supply with information questions at all stages of life cycle mechanical engineering are considered, and also quality indicators as complex property of a product are defined.
Keywords: компьютерная интеграция; качество изделия; оценка качества